UTERINE LEIOMYOMA: CLINICAL MANIFESTATIONS AND PERCEIVED IMPACT ON WOMEN’S HEALTH LIFE - THAMPI, AISWARYA; LAKSHMAN, AMRITHA; CHERIYAN, SHEBA MARY; SHARAF, SHIBILA; THOMAS, RAJEEV P; SHENOY T, HEERA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Uterine leiomyoma/uterine fibroid is the benign tumor of the smooth muscle of the uterus. This study was conducted to identify the clinical features and the effects on their quality of life factors with the occurrence of uterine fibroids. Methods: A cross-sectional study research design was used. The sample constituted 370 patients diagnosed with uterine fibroids, starting from November 2021 to May 2022. Results: Heavy menstrual bleeding was found to be the most common clinical manifestation seen in women with uterine leiomyoma. Hypothyroidism was seen to be associated with uterine leiomyoma. Generalized fatigue was the main issue faced by many along with difficulty to do daily chores. All these issues caused mental stress in women to a large extent. Conclusion: The associated factors, clinical manifestations, and perceived impact on women’s health life of uterine leiomyoma were studied. Age (41–60), overweight, and family history were the associated factors of uterine leiomyoma. Uterine fibroids negatively impacted the quality of life in women.